Biodiversidad marina de Costa Rica: Crustacea: Decapoda (Penaeoidea, Sergestoidea, Caridea, Astacidea, Thalassinidea, Palinura) del Pacífico - Vargas, Rita (1999)
A total of 1 1 7 species of shrimp and lobster are known from the Pacific coast of Costa Rica. They belong to the Suborders Dendrobranchiata, Superfarnily Penaeoidea (26 species) and Pleocyemata, Infraorder Caridea (73), Astacidea (one), Thalassinidea ( 1 3), and Palinura (four species). Twenty seven species (23%) are reported for the first time for Costa Rica. The distribution range of five species is extended, three of which are significant: Pontonía símplex (Holthuis, 1 95 1 ) from Tenacatitán B ay. México to Culebra Bay, Guanacaste; Veleronía serratifrons (Holthuis, 1 95 1 ) from La Libertad, Ecuador to Sámara, Guanacaste and Axiopsis serratifrons (A. Milne Edwards, 1 873) from Gorgona Island, Colombia to Culebra Bay, Guanacaste. Nine species, two of which are endernic, were described based on specimens collected in Costa Rica. Forty three percent of the tropical eastem Pacific species of shrimps are found on the Pacific coast of Costa Rica.